Institutional Reform for Irrigation and Drainage : Proceedings of a World Bank Workshop - Gonzalez, Fernando J.; Salman, Salman M.A. (Washington, DC: World Bank, 2013)
The report consists of an introduction, and three separate, but inter-related parts. The introduction provides an overview of the workshop discussions, arguing that the irrigation sector is blamed for many environmental problems, suggesting to set the right incentives, and regulations, including stakeholders involvement, and partnerships to overcome sector obstacles. The first part looks at the institutional diversity in irrigation, and drainage sectors, reviewing institutional changes within components of the Bank's portfolio of irrigation, and drainage projects. It addresses the extent to which the Bank's major policy documents of the 1990s have shaped the portfolio, and suggests recommendations to promote institutional changes, and the introduction of alternative solutions, such as private sector involvement, to increase competition, service contracts, and intergovernmental agreements. The second part reviews the irrigation regulatory framework, arguing that participation of Water Users Associations (WUAs) in the management of irrigation systems, is likely to increase systems efficiency, including improved collection of charges for irrigation infrastructure operation, and maintenance, as well as water charges. Legal instruments are further analyzed, to establish adequately functioning WUAs, including institutional issues for the potential privatization of irrigation management facilities. Also discussed is the legal pluralism, and its effect on water rights, highlighting interactions between multiple legal orders, and the fact that all such orders can provide bases for claiming property rights, suggesting the recognition of multiple bases for claims, regarding property rights as negotiated outcomes. The third part examines the benchmarking system, economic incentives, and pricing, discussing the role of economic incentives in improving water use efficiency, the benefits of benchmarking irrigation systems to sustain agricultural production, emphasizing on institutional, and structural reforms to overcome sector problems.